Observer 95. (Helsinki : The Museum of Contemporary Art, 1995)
Järvinen, The Wanderer (Juha ; Orava, Jukka ; Savolainen), Katja ; Cederholm, Parergon (Camilla ; Laine, Leenamaija ; Leppänen, Marianne ; Pilroinen, Juha ; Talonen), Topi ; Rantanen, The Cartoon Factory (Juha ; Kangas, Petri ; Pirttimaa), Ilkka ; Tammenpää, Click (Tuomo ; Koskinen, Mika Ilari ; Toijanniemi), Jaakko ; Alhola, Lemmikki Multimedia Software (Kate ; Inkari, Juha ; Karvo, Jouni ; Talonen, Topi ; Tähtinen), Jyri ; Putkonen, Vesa
Observer 95, The Museum of Contemporary Art, Helsinki, October 19 - November 11, 1995
boek